2022
DOI: 10.1002/hlca.202200060
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Scale Synthesis, Isolation and Characterisation of Sodium Organometallics:nBuNa and NaTMP

Abstract: Organolithium compounds represent one of the most widely utilised commodity reagents in synthetic chemistry. However, their analogues with the heavier alkali-metal sodium are much less utilised and their reactivity is less understood. Recent studies have shown the excellent potential of organosodium reagents in synthesis, finding widespread applications in cornerstone organic transformations such as deprotonative metalation, metal-halogen exchange or Pd catalysed CÀ C bond formation. However, detailed procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Organosodium complexes were first reported in 1858 by James Alfred Wanklyn, describing a reaction between ethyl iodide and sodium metal. , In the following centuries, despite discrete reports of their synthesis and structures, as well as their applications in organic, , inorganic, and polymer syntheses, organosodium chemistry is largely overshadowed by the dominating organolithium chemistry, which was first reported in 1917, nearly 60 years later than Wanklyn’s report in 1858. The underdeveloped status of organosodium chemistry was widely attributed to the highly reactive nature and the corresponding low thermostability of these complexes .…”
Section: Introductionmentioning
confidence: 99%
“…Organosodium complexes were first reported in 1858 by James Alfred Wanklyn, describing a reaction between ethyl iodide and sodium metal. , In the following centuries, despite discrete reports of their synthesis and structures, as well as their applications in organic, , inorganic, and polymer syntheses, organosodium chemistry is largely overshadowed by the dominating organolithium chemistry, which was first reported in 1917, nearly 60 years later than Wanklyn’s report in 1858. The underdeveloped status of organosodium chemistry was widely attributed to the highly reactive nature and the corresponding low thermostability of these complexes .…”
Section: Introductionmentioning
confidence: 99%
“…This method is very similar to the original procedure developed and reported by Schlenk in 1913 and subsequently used to isolate organolithium compounds in 1917 . More recently, the Hevia group have showcased the synthesis of useful organosodium reagents ( n BuNa and NaTMP) through a series of detailed and annotated photographs, which take advantage of a filter frit to isolate, wash, and dry highly pyrophoric solids …”
Section: Selected Schlenk Line Techniquesmentioning
confidence: 74%
“…In addition, it contains further details regarding Schlenk line equipment, assembly, cleaning, troubleshooting, and much more, and it is frequently updated with new guides and useful information. Other publications and resources that focus on the synthesis of air- and moisture-sensitive reagents, precursors, and catalysts are also available, many of which contain photographic step-by-step guides. , A number of books ,, and other resources detailing Schlenk line techniques and other advanced protocols such as vacuum line methods have been published; however, it should be noted that many of these resources are outdated and have access tolls (i.e., subscription and site licenses), and are therefore not well suited for teaching and training purposes.…”
Section: Pedagogy and Other Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that addition of TMEDA in hexane induces the deaggregation of NaTMP from a nonsolvated trimer to a dimer (Figure ), while addition of anisole to a mixture of NaTMP and TMEDA or PMDETA allows the isolation of mixed aggregates [(L) 2 Na 2 (TMP)­(C 6 H 4 –OMe)] (L = TMEDA, 3a ; L = PMDETA, 3b ) . These sodium mixed aggregates showed an incomplete metalation of anisole (36% after iodolysis), which was attributed to the equilibrium between the starting materials (L)­NaTMP and anisole with product 3 and TMP­(H) ( vide infra ).…”
mentioning
confidence: 98%